Increased function of pronociceptive TRPV1 at the level of the joint in a rat model of osteoarthritis pain. Issue 1 (23rd October 2013) - Kelly, S; Chapman, R J; Woodhams, S; Sagar, D R; Turner, J; Burston, J J; Bullock, C; Paton, K; Huang, J; Wong, A; McWilliams, D F; Okine, B N; et al.
Abstract : Objectives: Blockade of transient receptor potential vanilloid 1 (TRPV1) with systemic antagonists attenuates osteoarthritis (OA) pain behaviour in rat models, but on-target-mediated hyperthermia has halted clinical trials. The present study investigated the potential for targeting TRPV1 receptors within the OA joint in order to produce analgesia. Methods: The presence of TRPV1 receptors in human synovium was detected using western blotting and immunohistochemistry. In a rat model of OA, joint levels of an endogenous ligand for TRPV1, 12-hydroxy-eicosatetraenoic acid (12-HETE), were quantified using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Effects of peripheral administration of the TRPV1 receptor antagonist JNJ-17203212 on afferent fibre activity, pain behaviour and core body temperature were investigated. Effects of a spinal administration of JNJ-17203212 on dorsal horn neuronal responses were studied. Results: We demonstrate increased TRPV1 immunoreactivity in human OA synovium, confirming the diseased joint as a potential therapeutic target for TRPV1-mediated analgesia. In a model of OA pain, we report increased joint levels of 12-HETE, and the sensitisation of joint afferent neurones to mechanical stimulation of the knee. Local administration of JNJ-17203212 reversed this sensitisation of joint afferents and inhibited pain behaviour (weight-bearing asymmetry), to a comparable extent as systemic JNJ-17203212, in this model of OA pain, but did not alter core body temperature. There was no evidence for increased TRPV1 function in the spinal cord in this model of OA pain. Conclusions: Our data provide a clinical and mechanistic rationale for the future investigation of the therapeutic benefits of intra-articular administration of TRPV1 antagonists for the treatment of OA pain.